1996
DOI: 10.1111/j.1365-2389.1996.tb01401.x
|View full text |Cite
|
Sign up to set email alerts
|

The properties, genesis and significance of a man‐made iron pan podzol near Castletownbere, Ireland

Abstract: Beneath a layer of artificially deposited peat debris, an eluvial E horizon and thin iron pan (Bsm) has developed in the upper part of the Ap horizon of a brown podzolic soil (Haplorthod) near Castletownbere, Ireland. The thickness of the E horizon and the depth of the pan are directly related to the thickness of the layer of peat debris.The original soil (Haplorthod) was strongly podzolized with a significant accumulation of organic carbon, iron and aluminium in the spodic Bs. The iron pan of the upper sequum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“…Spodic horizons are base on the accumulation of organic C, Al, with or without Fe (Soil Survey Staff, 1999). Conry et al (1996) and Hseu et al (1999) also concluded that podzolization and placic horizon development were fundamentally different processes.…”
Section: Pedogenesis Of Placic Horizonmentioning
confidence: 94%
See 2 more Smart Citations
“…Spodic horizons are base on the accumulation of organic C, Al, with or without Fe (Soil Survey Staff, 1999). Conry et al (1996) and Hseu et al (1999) also concluded that podzolization and placic horizon development were fundamentally different processes.…”
Section: Pedogenesis Of Placic Horizonmentioning
confidence: 94%
“…Several hypotheses have been proposed to explain the genesis of placic horizons (Crompton, 1952;Clayden et al, 1990;Conry et al, 1996;Hseu et al, 1999;Lapen and Wang, 1999). Clayden et al (1990) concluded that placic horizon formed from Fe, which was reduced and mobilized from the upper part of the pedon and then reoxidized and precipitated in the Bs horizon.…”
Section: Pedogenesis Of Placic Horizonmentioning
confidence: 97%
See 1 more Smart Citation
“…It retards vertical leaching of water, inhibits the growth of roots and may cause plant mortality (Lapen & Wang, 1999; Wu & Chen, 2005). The wetness of surface layers above a placic horizon can create difficulties in land use (Conry et al , 1996), especially for forestry management. Placic horizons occur in a wide range of latitudes, from temperate to tropical, but are always associated with udic or perudic soil moisture regimes (McKeague et al , 1983; Hseu et al , 1999; Pinheiro et al , 2004; Schawe et al , 2007; Jien et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Pan layers are noted, if present. Iron pans are the most easily identifiable as a black to dark reddish coloured horizon, 2-10 mm thick (Conry, 1996;Cunningham et al, 2001). A score of -1 is assigned if a pan is present or 0 if not.…”
Section: Visual Drainage Assessmentmentioning
confidence: 99%